Avaliação da acessibilidade e da usabilidade de um modelo de ambiente virtual de aprendizagem para a inclusão de deficientes visuais - Mari, Carina Morais Magri (2011)
This work presents collaborations of the ergonomics for the virtual learning environment, for its configuration and its use, seeking the inclusion of people with visual disabilities. These collaborations go along with the cognitive principles of ergonomics in which the focus is on the aspects of the usability and accessibility of interfaces of such environments. The virtual learning environment used was Moodle which is applied at Universidade Federal de São Carlos in order to offer distance education courses and where a visually impaired student takes subjects from the technological sugar-cane alcohol production course. The aim of this work is to analyse the interfaces under the view of accessibility, usability and ergonomics so as to facilitate the usage of the virtual learning environment from visually disabled students, contributing to the improvement of the UFSCar‟s distance education system, providing opportunity of inclusion to people with visual disabilities concerning distance education.